Human mesenchymal stem cells as a two-edged sword in hepatic regenerative medicine: engraftment and hepatocyte differentiation versus profibrogenic potential. Issue 2 (16th July 2007) - di Bonzo, L Valfrè; Ferrero, I; Cravanzola, C; Mareschi, K; Rustichell, D; Novo, E; Sanavio, F; Cannito, S; Zamara, E; Bertero, M; Davit, A; Francica, S; et al.
Abstract : Background and aim: Mesenchymal stem cells from bone marrow (MSCs) may have the potential to differentiate in vitro and in vivo into hepatocytes. We investigated whether transplanted human MSCs (hMSCs) may engraft the liver of non-obese diabetic severe combined immuno-deficient (NOD/SCID) mice and differentiate into cells of hepatic lineage. Methods: Ex vivo expanded, highly purified and functionally active hMSCs from bone marrow were transplanted (caudal vein) in sublethally irradiated NOD/SCID mice that were either exposed or not to acute liver injury or submitted to a protocol of chronic injury (single or chronic intraperitoneal injection of CCl4, respectively). Chimeric livers were analysed for expression of human transcripts and antigens. Results: Liver engraftment of cells of human origin was very low in normal and acutely injured NOD/SCID mice with significantly higher numbers found in chronically injured livers. However, hepatocellular differentiation was relatively rare, limited to a low number of cells (ranging from less than 0.1% to 0.23%) as confirmed by very low or not detectable levels of human transcripts for α-fetoprotein, CK18, CK19 and albumin in either normal or injured livers. Finally, a significant number of cells of human origin exhibited a myofibroblast-like morphology. Conclusions: Transplanted hMSCs have the potential to migrate into normal and injured liver parenchyma, particularly under conditions of chronic injury, but differentiation into hepatocyte-like cells is a rare event and pro-fibrogenic potential of hMSC transplant should be not under-evaluated.